KONSEP BERPOLIGAMI PERSPEKTIF MADZHAB SYAFI’I DAN KOMPILASI HUKUM ISLAM - Muhammad Alwy Asy-Syif Hadiyulloh; ibnu Jazari; Syamsu Madyan (Jurnal Hikmatina, 2022)
According to the Big Indonesian Dictionary, polygamy is a marriage system in which one party owns or marries several members of the opposite sex at the same time. This research is a type of research (library research). That is a study that seeks to explore theories that have developed in the field of science related to a problem, look for methods, and research techniques both in collecting data or analyzing research that has been used by previous researchers, obtaining a broader orientation in selected problems and avoid unwanted duplication by leading to the development of existing concepts and facts. The terms of justice in polygamy are also expressed by the priests of the madzhab including Imam Syafi'i. In the case of polygamy a husband may have more than one wife but is limited to four wives. However, this permissibility has a condition that is to be fair between the women, either from a living or in turn. In this case, Imam Syafi'i added, another condition that must be emphasized is that the husband must be able to guarantee the rights of his wife and children